2021
DOI: 10.1002/chem.202102926
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Near‐Infrared Electrochemiluminescence from Au18 Nanoclusters

Abstract: Bright, near-infrared electrochemiluminescence (NIR-ECL) of Au 18 nanoclusters is reported herein. Spooling ECL and photoluminescence spectroscopy were used to track and link NIR emissions at 832 and 848 nm to three emissive species, Au 18 0 *, Au 18 1 + * and Au 18 2 + *, with a considerably high ECL efficiency of 5.5 relative to that of the gold standard Ru(bpy) 3 2 + /TPrA (with 5-6 % reported ECL efficiency). The unprecedentedly high efficiency is due to the overlapped oxidation potentials of Au 18 0 and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…The 45 nm difference between the onset peak wavelength and the maximum intensity wavelength is probably due to the formation of different excited states of Cu NCs in the process of potential negative scanning as the valence state of the obtained Cu NCs is between 0 and +1 as demonstrated from XPS. Although it is hard to decide the exact content of Cu(0) and Cu­(I) in the obtained Cu NCs, a series of similar valence-state-dependent ECL emission wavelength investigations on gold nanoclusters have been concluded by the Ding group. , Upon sweeping the potential further negative and backwards, the ECL intensity decreased owing to the depletion of the Cu NCs –• and SO 4 –• species and led to the ECL devolution (Figure C).…”
Section: Experimental Sectionmentioning
confidence: 72%
See 1 more Smart Citation
“…The 45 nm difference between the onset peak wavelength and the maximum intensity wavelength is probably due to the formation of different excited states of Cu NCs in the process of potential negative scanning as the valence state of the obtained Cu NCs is between 0 and +1 as demonstrated from XPS. Although it is hard to decide the exact content of Cu(0) and Cu­(I) in the obtained Cu NCs, a series of similar valence-state-dependent ECL emission wavelength investigations on gold nanoclusters have been concluded by the Ding group. , Upon sweeping the potential further negative and backwards, the ECL intensity decreased owing to the depletion of the Cu NCs –• and SO 4 –• species and led to the ECL devolution (Figure C).…”
Section: Experimental Sectionmentioning
confidence: 72%
“…On the basis of these concerns, metal nanoclusters stand out owing to their inherent electrochemical and photochemical features along with low toxicity and excellent biocompatibility. Importantly, Ding and co-workers have performed advanced ECL investigations on gold nanoclusters (Au NCs), in which highly efficient ECL emission in the NIR region was observed with unprecedented ECL efficiency as high as 3.5-, 5.5-, and 270fold stronger than that of standard Ru(bpy) 3 2+ from Au 38 NCs, 13 Au 18 NCs, 14 and Au 21 NCs, 15 respectively. In another recent work, Chen et al 16 found very intense NIR ECL generated from a novel rod-shaped bimetal Au 12 Ag 13 NCs, exhibiting a tripropylamine coreactant ECL that is 400 times higher than that of the Ru(bpy) 3 2+ reference.…”
mentioning
confidence: 99%
“…1,2,18 The ECL waveband of AuNCs can be conveniently tuned by adjusting the capping agent, 19−21 doping the Au core with other metals, 11,22,23 and changing the valence state of the body element Au. 3,24−26 Moreover, the ECL of AuNCs can be conveniently, and even synchronously, 27 generated in bandgap-engineered ECL 17,28 and surface-defect-involved routes. 21,29 Although many biosensing strategies have been proposed with AuNCs as ECL luminophores, 9,12,23,30 the role of body element Au on the ECL generation of AuNCs is still far from clear.…”
Section: Introductionmentioning
confidence: 99%
“…Unary Au nanoclusters (NCs) are promising nanomaterials with high biocompatibility, excellent stability, and fascinating optical, electrical, as well as chemical properties. AuNCs are also a kind of ECL luminophore candidate with excellent performance for both fundamental and applied investigation, which is anticipated to be an alternative to both II–VI nanoparticles and molecular ECL luminophores. ,, The ECL waveband of AuNCs can be conveniently tuned by adjusting the capping agent, doping the Au core with other metals, ,, and changing the valence state of the body element Au. , Moreover, the ECL of AuNCs can be conveniently, and even synchronously, generated in band-gap-engineered ECL , and surface-defect-involved routes. , Although many biosensing strategies have been proposed with AuNCs as ECL luminophores, ,,, the role of body element Au on the ECL generation of AuNCs is still far from clear.…”
Section: Introductionmentioning
confidence: 99%
“…Unary metal NCs are a kind of NPs of a few to several tens atoms; their low or nontoxicities and high biocompatibilities are promising to develop and design toxic-element-free ECL luminophores. , To the best of our knowledge, although only very limited unary metal NCs, such AuNCs, can be highly passivated to give off bandgap-engineered ECL of a single color, some investigation has provided unambiguous evidence that single-color ECL can be conveniently achieved from metal NC luminophores via completely blocking the bandgap-engineered route. ,, The unary metal NCs with single-color ECLs in the surface-defect-involved route might provide an alternative to molecular ECL luminophores for ECL evolution. ,, Jia et al proposed a dual-stabilizer-capped strategy to synthesize AuNCs with single-color and surface-defect-involved ECL around 860 nm . Zhai et al designed a doping growth strategy to prepare BSA-capped Au–Ag bimetallic NCs with surface-defect-involved and single-color ECL around 794 nm .…”
mentioning
confidence: 99%